Internalisasi Nilai Kehormatan Qur’ani-Hadisi sebagai Upaya Penguatan Moral Gen Z di Tengah Tantangan Pergaulan Bebas - Ummu Aisyah; Nasrulloh (Al-Kindi, 2026)
The increase in promiscuous behavior among Gen Z shows a gap between the ideal values of honor in the Qur'an and Hadith and modern social reality, so moral reinforcement through the internalization of religious values is needed. This study aims to analyze Gen Z's level of understanding of Qur'anic-Hadith values of honor, the influence of internalizing these values on moral behavior, and the supporting and inhibiting factors. Using a quantitative-descriptive method through a survey of 12 respondents and based on Hirschi's Social Control Theory and Bandura's Social Learning Theory, the study found that the majority of Gen Z understood the concept of ḥifẓ al-‘ird and the prohibition of adultery well, and 83% stated that honor values greatly influenced their interactions with the opposite sex. while all respondents assessed that the internalization of religious values was able to suppress deviant behavior. The main supporting factors included family role models and guidance from religious teachers, while the biggest obstacles came from a permissive social environment and exposure to digital media. These findings confirm that the internalization of Qur'anic-Hadith values of honor is a strategic instrument in strengthening the morals of Gen Z amid the challenges of free socializing in the digital age.